EFFECT OF VENLAFAXINE AND VITAMIN C ON SOME BIOCHEMICAL PARAMETERS OF SACCHAROMYCES CEREVISIAE (NRRLY-12632) - Çakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2025)
In this study, Saccharomyces cerevisiae (NRLLY-12632) was grown in Yeast Extract–Peptone–Dextrose (YPD) medium containing different concentrations of venlafaxine, (RS)-1-[2-dimethylamino-1-(4-methoxyphenyl)-ethyl] cyclohexanol. To counteract the effect of venlafaxine, vitamin C were added to the growth medium of Saccharomyces cerevisiae (S. cerevisiae). Then the antioxidant enzymes activities and stress biomarkers were investigated through the use of spectrophotometric methods and HPLC technique, respectively. Addition of venlafaxine in to growth medium of S. cerevisiae, significantly increased the superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione reductase (GSH-Rd) and peroxidase (POD) activities (p?0.05). On the other hand, activities of CAT, GSH-Px, GSH-Rd and POD enzymes were decreased significantly in all vitamin C concentrations added to the growth medium containing venlafaxine (p?0.05). SOD activities were found to be significantly decreased at 50 and 75 ppm vitamin C concentrations (p?0.05). While total protein amount decreased at all venlafaxine concentrations, on the other hand amount of advanced oxidized proteins (AOP) increased significantly (p?0.05). Vitamin C at 25, 50 and 75 ppm concentrations with venlafaxine led to increase the total protein amount and decreased the AOP concentration (p?0.05). The amount of reduced glutathione (GSH) decreased in all venlafaxine concentrations while the amounts of oxidized glutathione (GSSG), malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) increased (p?0.05). With the addition 25, 50 and 75 ppm vitamin C to the growth medium containing venlafaxine while leading to decrease the amount of GSSG, MDA and 4-HNE, the amount of GSH increased significantly (p?0.05). From these findings, it can be said that the negative effect of venlafaxine on the biochemical parameters of S. cerevisiae is reduced by the addition of vitamin C to the medium.
Keywords: Vitamin C; Antioxidant enzymes; S. cerevisiae; Venlafaxine; Stress biomarkers.